2020
DOI: 10.1111/1541-4337.12535
|View full text |Cite
|
Sign up to set email alerts
|

Typical reactive carbonyl compounds in food products: Formation, influence on food quality, and detection methods

Abstract: Reactive carbonyl compounds are a large group of highly reactive electrophilic compounds containing one or more carbonyl groups, which can be created by lipid oxidation both in vivo and in food. Malondialdehyde (MDA) and 4‐hydroxy‐2‐nonenel (HNE) are the two most important reactive carbonyl compounds in food. They can react with proteins and nucleic acids and cause biological damage to cells and lead to carbonyl stress. Therefore, they are regarded as representative products of lipid oxidation, toxic molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 168 publications
(189 reference statements)
0
17
0
Order By: Relevance
“…The oxidation of meat protein is always triggered by lipid oxidation [ 4 ]. Malondialdehyde (MDA) is the main lipid oxidation product in meat and meat products [ 5 ]. MDA contains two highly reactive carbonyl groups that can attack nucleophilic amino acid side chains, leading to oxidative damage of proteins [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of meat protein is always triggered by lipid oxidation [ 4 ]. Malondialdehyde (MDA) is the main lipid oxidation product in meat and meat products [ 5 ]. MDA contains two highly reactive carbonyl groups that can attack nucleophilic amino acid side chains, leading to oxidative damage of proteins [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can be produced by lipid peroxidation. The primary products of lipid oxidation, such as conjugated dienes and hydroperoxides, may be indicators of the initial stage of oxidative degradation (Zhou et al., 2020). In the current study, however, 2,4‐octadiene was not found to be a chemical indicator for any species.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that diacetyl production is increased with aeration (Dillon, 2014) and mahi‐mahi are mostly found in the surface water. Moreover, mono‐ketones could be gradually derived from hydroperoxides through the splitting of fatty acid chains (Zhou et al., 2020). It was found that 2‐heptanone and 3‐hexanone were not possible chemical indicators of decomposition for any species, while others (2‐butanone, 2‐nonanone, 2‐pentanone, 2‐undecanone, 3‐pentanone, and 3‐methyl‐2‐butanone) could be chemical indicators for certain species.…”
Section: Resultsmentioning
confidence: 99%
“…The CV of fried sample was significantly increased to 49.95 μmol/g after heating at 200°C for 8 min compared with the fresh grass carp fillets (20.03 μmol/g). According to ISO 2200, the maximum allowable CV in frying oil was 50 μmol/g (Zhou et al., 2020). Volatile substances including aldehydes and ketones in the fish meat during frying were produced by the oxidation of fish oil.…”
Section: Resultsmentioning
confidence: 99%